Hungarian Monitoring, 3 October 1989 . [Magyar rádiófigyelő], 1989. október 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Thousands of East German refugees in Prague and Warsaw embassies - Reaction to the refugee affair in the GDR - Polish United Workers' Party looks for a way out of the crisis - Warsaw Pact united armed forces' military council convenes in Warsaw - Slovenian modification of the constitution Domestic Affairs: - Hungary at the Council of Europe sessions - László Lengyel on the Hungarian Democratic Forum (MDF)'s electoral chances - Guessing the future of Hungarian Socialist Workers' Party (MSZMP) - Germans in Hungary request their rehabilitation - Hungarian Calvinist church's intercession on behalf of László Tőkés - Hungarian Academy of Sciences joins in research into the fate of Sándor Petőfi Economy: - EEC economic committee talks in Budapest Külpolitika: - Kelet-német menekültek ezrei a prágai és varsói nagykövetségen - A menekültügy visszhangja az NDK-ban - A LEMP keresi a válságból kivezető utat - Varsóban összeült a VSZ egyesített fegyveres erőinek katonai tanácsa - A szlovén alkotmánymódosítás Belpolitika: - Magyarország az Európa Tanács ülésein - Lengyel László az MDF választási esélyeiről - Találgatások az MSZMP jövőjéről - Rehabilitálásukat kérik a magyarországi németek - A magyarországi református egyház közbenjárása Tőkés László érdekében - Az Akadémia bekapcsolódik Petőfi sorsának kutatásába Gazdaság: - Az EGK gazdasági bizottságának budapesti tárgyalása